De la campagne à la ville à la recherche de protection : Le cas colombien du déplacement forcé - Osorio Pérez, Flora Edilma (Refuge: Canada’s Journal on Refugees, 2007)
This article discusses some dynamics of internal forced displacement, which has occurred at a high level in Colombia over the last decade as a result of the civil war which the country is going through. Influenced by the rural-urban population flow, peasants flee from their homes to the imagined safety and security of the cities. Bogotá, for example, the seat of government and of all public institutions, is experiencing rapid urbanization, as distinct from a de-ruralization process which is transforming the whole country. When displaced people are able to meet with others in similar circumstances they are able to establish new improvised ties of sociability, fragmented and ambiguous as they are, and enables them to find some solutions to their circumstances. Despite the precariousness that each day brings, the desplazados (displaced) live in expectation of a better future, despite having no other place to go and being surrounded by a weariness caused by instability and uncertainty.